STRUCTURAL RELATIONSHIPS IN (MN1-XZNX)MN2O4 (O≤×≤0.26): THE "DRAGGING EFFECT" OF THE TETRAHEDRON ON THE OCTAHEDRON - Bosi F.; Lucchesi S.; Della Giusta A. (My University, 2002)
Ten hausmannite crystals (from Ilfeld and Friedrichrode, Harz, Germany), belonging to the (Mn1-xZnx)Mn2O4 (O ≤ × ≤ 0.26) system (141/amd hausmannite structure type), were characterized by chemical (electron microprobe) and structural (single-crystal X-ray diffractometer) analysis. The prevailing trivalent cation is Mn3+, with very minor Al (not higher than 0.005 apfu). Among divalent cations, the main substitution involves Zn → Mn2+. Cation distribution was obtained by comparing chemical and structural data, and results confirm normal distribution, with Mn3+ ordered on the octahedral site. A specific bond distance of 2.030 Å was refined for VIMn3+-O. Unit-cell parameters a and c range from 5.752 to 5.763 Å and from 9.408 to 9.461 Å, respectively. The smallest values are characteristic of the sample with the highest hetaerolite content. T-O bond distance (2.027-2.041 Å) shows a strong positive correlation with unit-cell constants, while the O-T-O angle (103.3-103.7°) is related only to the oxygen coordinate, z. The two octahedral bond distances show limited variations: the shorter one, M-Os, ranges from 1.927 to 1.930 Å, and is not significantly correlated with unit-cell parameters. The longer one, M-OL, shows a larger variation, from 2.281 to 2.290 Å, and is positively correlated with c. Regularization of the octahedron with increasing hetaerolite content coincides with an increase in the oxygen coordinate y and a decrease in c and c/a. Of particular interest is the positive linear relation between octahedral elongation and VT. As the octahedral content of all samples is almost constant, given the closeness of Mn3+ to stoichiometry, all structural distortions are linked to VIZn→IVMn2+ that reduces the T-O bond distance and causes movement of the structure toward cubic symmetry. This interaction is due to the "dragging effect" of the tetrahedron on the octahedron. In hausmannite-type structures, besides the main structural distortion produced by the Jahn-Teller effect, a secondary one, without symmetry modification, is determined by the geometrical effects of the tetrahedron on the octahedron.